IbM BAGI GURU MATEMATIKA SMPDI KABUPATEN KENDAL - Rasiman .; Kartinah .; Dina Prasetyowati (E-Dimas: Jurnal Pengabdian kepada Masyarakat, 2014)
Abstract Community service activities for this, intended for junior high school mathematics teachers, especially in MGMPs Kendal in support of Curriculum 2013. The 2013 curriculum is implemented in stages beginning in school year 2013-2014 through the implementation is limited, especially for schools that are ready to implement it. In the academic year of 2013/2014, Curriculum 2013 implemented on a limited basis for Class I and IV Elementary / Madrasah Ibtida'iyah (SD / MI), Class VII School SMP / MTs (SMP / MTs), and Class X High School / School SMK / Madrasah Aliyah (SMA / SMK / MA / MAK). In the academic year of 2015/2016 is expected toCurriculum 2013 has been implemented in the whole class I to Class XII. For that we consider necessary the holding of training activities and workshops preparation of lesson plans and training curriculum in 2013 based learning media creation software GeoGebra useful for teachers of Mathematics junior in Kendal. The method used is the training and workshops with a target output of each participant design a lesson plan curriculum in 2013 and the manufacture of Mathematics instructional media with the help of software GeoGebra. Keywords: Curriculum 2013, GeoGebra